Pelvic Floor Muscle Training in Female Athletes: A Randomized Controlled Pilot Study - Pires, Telma Filipa; Pires, Patricia Maria; Moreira, Maria Helena; Gabriel, Ronaldo Eugênio Calçadas Dias; João, Paulo Vicente; Viana, Sara Alexandra; Viana, Rui Antunes (International Journal of Sports Medicine, 2020)
The aim of this study was to investigate the effects of pelvic floor muscles training in elite female volleyball athletes and whether it is an effective therapy for stress urinary incontinence. Fourteen athletes, both continent and incontinent, between 18 and 30 years of age, were randomly assigned to an experimental group or a control group. The experimental group received a protocol for pelvic floor muscle training for 4 months. This consisted of three phases: awareness/stabilization, strength training and power. The control group was not subject to any intervention during the same period. Measures were collected at the initial and final phase for both groups. Maximum voluntary contractions were evaluated with a perineometer, involuntary urine loss with a Pad test and quality of life with the King’s Health Questionnaire. Baseline sociodemographic and anthropometric characteristics were not significantly different. Comparing the two groups, the experimental group improved maximum voluntary pelvic contractions (p<0.001) and reduced urine loss (p=0.025), indicating the existence of significant differences between groups in the variation from the initial and final phases. The percentage of urine loss decreased in the experimental group, from 71.4–42.9%, suggesting that the protocol intervention for 16 weeks may help athletes with stress urinary incontinence.
Keywords: elite female athletes; pelvic floor muscle training; maximum voluntary contractions; stress urinary incontinence